2020
DOI: 10.1186/s13244-020-0835-2
|View full text |Cite
|
Sign up to set email alerts
|

The added value of digital breast tomosynthesis in improving diagnostic performance of BI-RADS categorization of mammographically indeterminate breast lesions

Abstract: Background: Mammographic findings are seen more clearly in tomographic images with consequent improvement of Breast Imaging Reporting and Data System (BI-RADS) in categorization of indeterminate breast lesions. This study aimed to evaluate the added value of digital breast tomosynthesis (DBT) to BI-RADS classification in categorization of indeterminate breast lesions after digital mammography (DM) as an initial approach. Methods and results: We prospectively evaluated 296 women with BI-RADS indeterminate breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…Also, the reduction in the number of BIRADS 3 count lesions by 33% (from 103 to 45), which was more significant for asymmetries and distortions is one of the potential advantages of DBT. Similar results were obtained by Basha [11], who reported DBT produced 31.5% upgrading and 35.2% downgrading of BI-RADS scoring of breast lesions. Also DBT reduced number of BI-RADS 3 and 4, compared to FFDM (p < 0.001).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, the reduction in the number of BIRADS 3 count lesions by 33% (from 103 to 45), which was more significant for asymmetries and distortions is one of the potential advantages of DBT. Similar results were obtained by Basha [11], who reported DBT produced 31.5% upgrading and 35.2% downgrading of BI-RADS scoring of breast lesions. Also DBT reduced number of BI-RADS 3 and 4, compared to FFDM (p < 0.001).…”
Section: Discussionsupporting
confidence: 88%
“…In a similar study conducted by Basha MA et al, [11] concluded that BIRADS with DBT was significantly superior to BIRADS with DM in breast cancer diagnosis (AUC: 0.883 vs. 0.619; p < 0.0001; 95% CI 0.214 to 0.313), and the BI-RADS with combined DM and DBT was significantly superior to BI-RADS with DM alone or BIRADS with DBT alone (AUC: 0.971; p < 0.0001; 95% CI 0.0565 to 0.120) Ali et al [22] concluded that 3D DBT significantly reduced the need for additional mammographic views and as well the frequent follow-up studies as it gave better characterization for all BIRADS 3 lesions and reduced the stress levels in women. And that scrolling the three-dimensional images for a particular view eliminates the tissue overlap seen in two-dimensional images and improves the resolution for a better diagnostic capability.…”
Section: Discussionmentioning
confidence: 64%
“…1 ). Finally, 20 articles with 44513 patients and 58388 lesions fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Table 1 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 50% were conducted in Asian countries [ 18 19 20 23 25 27 29 31 32 33 ], and there were four prospective studies [ 18 19 32 33 ]. Five studies had patients with breast density ≥ 2 or b according to American College of Radiology (ACR) [ 28 29 30 31 34 ], nine studies consecutively sampled participants [ 18 21 22 24 25 26 32 34 35 ], and 13 studies performed a per-lesion analysis [ 18 19 20 21 22 23 25 26 28 29 31 32 33 34 ]. Five studies included lesions without calcifications [ 26 28 29 30 34 ], and three studies symptomatic patients only [ 19 29 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation